2021
DOI: 10.1108/ijefm-10-2020-0060
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support on episodic volunteers' affective and behavioral outcomes: a case of the 2016 Rio Olympic Games

Abstract: PurposeThe aim of this study was to investigate the effects of perceived organizational support (POS) on the relationships between volunteer job satisfaction, attitude toward volunteering and continuance intention. Also, this study investigated the moderating role of volunteer age in the relationships between study variables.Design/methodology/approachParticipants were recruited from volunteers in the Rio 2016 Olympic Games and/or the Rio 2016 Paralympic Games (N = 4,824). Data were primarily analyzed using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…The same as , training and working conditions, as conditions provided by the event, can significantly affected the sports event volunteers' satisfaction and work engagement in volunteerism. Different from the direct effect of organizational support on volunteers' satisfaction and behavior (Won et al, 2021), the results also indicated that sports event volunteer management practices indirectly affected the volunteers' attitude and behavior, which is also verified by . This effect may have been mediated by some intermediate factors such as social capital, which is a different mediating variable from previous study .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The same as , training and working conditions, as conditions provided by the event, can significantly affected the sports event volunteers' satisfaction and work engagement in volunteerism. Different from the direct effect of organizational support on volunteers' satisfaction and behavior (Won et al, 2021), the results also indicated that sports event volunteer management practices indirectly affected the volunteers' attitude and behavior, which is also verified by . This effect may have been mediated by some intermediate factors such as social capital, which is a different mediating variable from previous study .…”
Section: Discussionmentioning
confidence: 73%
“…Sports volunteer management practices and organizational support can affect volunteers’ attitude and behavior (Cho et al, 2020; Wicker, 2017; Won et al, 2021). These management practices include decision making (Cuskelly & O’Brien, 2013), support from the organization (Cuskelly & Hope, 2013), financial resources (Coates et al, 2014), role models (Wicker & Frick, 2016), communication modes, the control of volunteers (Byers, 2013), rewards and recognition (Cho et al, 2020), training (T.…”
Section: Discussionmentioning
confidence: 99%
“…Employees' job satisfaction is a concern among organizational psychologists because it is an attitudinal variable that describes the feeling of an individual about his/her job (Chiboiwa et al, 2011;Knights & Kennedy, 2005) and is associated positively with productivity and negatively with absenteeism in the workplace (Lo Presti, 2013). Job satisfaction in the context of NPOs is important because volunteers who are happy with their work activities are likely to keep on volunteering (S. E. Usadolo & Usadolo, 2018;Won et al, 2021).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Job satisfaction in the context of NPOs is important because volunteers who are happy with their work activities are likely to keep on volunteering (S. E. Usadolo & Usadolo, 2018; Won et al, 2021).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…According to Liu et al (2016) perceived organizational support is an employee's assessment of compensation issues from the workplace or a description of the quality of employees where the employee works. The better Perceived Organizational Support can be seen from the feeling of being treated fairly, encouragement from superiors, rewards that are supported by employees, as well as pleasant busy situations can manifest the positive character of individual employees at work (Won, Chiu, Bang, and Bravo, 2021). According to Ibrahim et al (2016) perceived organizational support has a significant effect on employee creativity because it increases motivation on organizational performance and efficiency.…”
Section: Introductionmentioning
confidence: 99%